Analisis Performa Sistem pada Pemisahan Database Analitik dengan Transaksional - Santosa, I Made Ari Madya; Cahyadi Putra, I Gusti Ngurah Anom (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2023)
The speed and efficiency of a system at this time has a very important role. Currently there are several solutions to answer these challenges, one of which is to separate the database on the system. In this study, an analysis was carried out on the separation of databases on a transactional and analytic system. Analysis is carried out with a research flow that begins with problem identification followed by sampling data on technology companies that have transactional systems, then implementing transactional and analytical programs on microservices architecture, conducting tests with Load-Testing, followed by analysis of test results and then drawing conclusions. After conducting research in accordance with the research flow, it was concluded that the separation of databases on transactional and analytic systems is better for producing faster system performance compared to transactional and analytic systems using the same database.